Utilization of the out of hours service in Poland: an observational study from Krakow - Tomasik Tomasz; Windak Adam; Margas Grzegorz (BMC, 2008)
Abstract Background In 2000 a new GP contract was introduced in Poland. It allowed GPs to subcontract out of hours care to specialized deputizing services. One such service in Kraków provides care to 61 GP practices with a population of 420 000 inhabitants. The aim of this study is to analyze seasonal and geographical variation in out of hours care use and to find the most important factors influencing it. Methods Routinely collected data for 24 months (2003-2004) containing type, date and time of the contacts were used. Results During the study period 238 072 contacts were recorded: 149 911 ambulatory doctor visits, 23 434 home visits and 64 727 nurse procedures. The mean rate of out of hours contacts was: for ambulatory visits 178 per 1000 inhabitants/year (varied between practices from 9 to 696), for home visits 28 (from 1 to 36) and for nurse procedures 77 (from 3 to 327). The highest rate of ambulatory visits was 739 in the age group 0-4, the lowest - 104 in the age group 45-49. The highest rate of home visits was 221 in the age group over 85. The rate of ambulatory GP visits and nurse procedures was negatively correlated with the distance between the location of GP practice and the nearest out of hours clinic. The rate of home visits was positively correlated with the age of the patient. Conclusion Significant differences between practices suggest that non medical factors may play an important role in the patient's decision to see a GP when the surgery is closed. Their influence should be limited to make the system more efficient.